Cevaplar

  • Eodev Kullanıcısı
2013-01-15T00:28:08+02:00

f(1)=a.1+b=a+b

 

f'(x)=x-b/a            f'(3)=3-b/a=4 t        ise 3-b=4a  

 

                              f'(2)=2-b/a=5       ise  2-b=5a   -ile carpıp toplarsak  

                                                                 +.............................

 

                                                                 1=-a  olur  a =-1 olur          denklemde koyarsak 

 

                                                                             2-b=5.-1=-5

                                                                             2=-5+b                       b=7   olur

 

 

f(x)=ax+b

f(1)=-1.1+7=6 cıkar sonuc

 

 

 

 

 

 

 

 

 

      

1 5 1